The influence of judical practice on the Legislation in the Sphere of LGBT Community Rights - Čović, Ana (Sociološki pregled, 2021)
In the light of the announced adoption of the Law on Same-Sex Unions, the question arises whether the draft law is in accordance with the Constitution, especially after the announcements that the law will not be signed. Although the Constitution specifies that marriage is a union of a man and a woman, experts point out that in this case it is not a law on marriage and family, nor does it provide for the possibility of adoption of children by same-sex couples, but that it regulates property, health, pension and other legal relationships of same-sex partners living in the union. At the same time, many public figures have invited traditional religious communities to react in order to defend the “right to freedom and future of the people”, emphasizing that contentious issues related to the regulation of mutual rights and obligations of same-sex couples could be resolved by amending the existing laws in those areas. In the countries where similar laws exist, case law has played a significant role, just as various medical and psychological associations. The European case law is not uniform, and cases often end before the European Court of Human Rights, while in the United States at the federal level, all anti-homosexual laws are repealed by a Supreme Court decision (Lawrence v. Texas, 539 U.S. 558 [2003]). Nevertheless, there is no single law in this area and the rights of same-sex couples vary from country to country. The paper will provide an overview of significant court decisions in this area in European countries, as well as the decisions of the US Supreme Court, which may lead us to think about the possible legal consequences of (non)adoption of the disputed Law on Same-Sex Unions, about procedures that could be initiated if partners decided to request judicial protection for the purpose of recognizing their guaranteed human rights, as well as the content and significance of such court judgments.